2020
DOI: 10.1177/0363546520951796
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Outcomes of Anterior Cruciate Ligament Reconstruction With Hamstring Tendon Graft and Femoral Cortical Button Fixation at Minimum 20-Year Follow-up

Abstract: Background: The short-term outcomes of anterior cruciate ligament (ACL) reconstruction with bone–patellar tendon–bone or hamstring tendon (HT) graft are excellent with good clinical stability and patient-reported outcomes. Although some studies have reported the long-term outcomes of bone–patellar tendon–bone graft ACL reconstruction, few have reported the outcomes of HT graft ACL reconstruction. Purpose: To assess clinical and radiographic outcomes of HT graft ACL reconstruction with femoral cortical button f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 46 publications
1
16
1
Order By: Relevance
“…Previous studies have shown that signs of OA are present in 10% to 90% of patients at 10 to 20 years after an ACL injury. 11 , 18 , 21 The identification of patients with early-onset OA is crucial to prevent or minimize further harm to the knee joint, and this could aid in developing treatment options for early OA. However, before clinical signs become apparent, OA has already been initiated.…”
mentioning
confidence: 99%
“…Previous studies have shown that signs of OA are present in 10% to 90% of patients at 10 to 20 years after an ACL injury. 11 , 18 , 21 The identification of patients with early-onset OA is crucial to prevent or minimize further harm to the knee joint, and this could aid in developing treatment options for early OA. However, before clinical signs become apparent, OA has already been initiated.…”
mentioning
confidence: 99%
“…Two other studies were prospective case-control studies comparing different autografts 31 or comparing nonoperative versus operative treatment 33 ; in the latter case, patients treated nonoperatively were not included in the analysis. A further 6 studies were prospective case series, 17 , 19 , 26 28 , 37 and 5 studies were retrospective case series. 9 , 10 , 20 , 23 , 36 The 74 patients who received hamstring tendon grafts in the comparative study by Thompson et al 31 were excluded from the analysis because they were already accounted for in another study from the same authors evaluating 200 ACLRs with hamstring tendons 27 ; however, data from Thompson et al 31 were used if not available in the complete series.…”
Section: Resultsmentioning
confidence: 99%
“…OA was evaluated in 14 studies ‡‡ including 1330 patients: The radiographic IKDC score was used in 7 studies 9 , 10 , 23 , 27 , 28 , 31 , 36 ; the Kellgren-Lawrence classification, in 4 studies 17 , 26 , 33 , 37 ; and the Ahlbäck classification, in 3 studies 6 , 11 , 29 ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…We know that the long-term outcomes for ACL reconstruction patients are greatly influenced by the status of the meniscus and that patients with partial meniscectomy have lower subjective scores and greater rate of osteoarthritis. [8][9][10][11][12] Given this information, some surgeons continue to repair MMTs that are degenerative in nature and extend into the avascular zone. [13][14][15][16][17] Shelbourne and Carr 16 evaluated patients who had unstable bucket-handle MMTs that were either repaired or removed at ACL reconstruction.…”
Section: See Related Article On Page 3500mentioning
confidence: 99%